A systematic review and meta-analysis of within-person changes in cardiac vagal activity across the menstrual cycle: implications for female health and future studies - Schmalenberger, Katja; Eisenlohr-Moul, Tory A.; Würth, Lena; Schneider, Ekaterina; Thayer, Julian F.; Ditzen, Beate; Jarczok, Marc N. (Journal of Clinical Medicine, 2019)
Interest in cardiac vagal activity (CVA; e.g., parasympathetically-mediated heart rate variability) as a biomarker of physical and mental health has increased exponentially in recent years. However, the understanding of sources of within-person change (i.e., intra-individual variance) in CVA is lagging behind. This systematic review and meta-analysis summarizes and quantifies current empirical evidence of within-person changes in measures of CVA across the menstrual cycle in naturally-cycling premenopausal females. We conducted an extensive literature search following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement in five databases to identify observational studies with repeated measures of CVA in at least two menstrual cycle phases. A broad meta-analysis (nstudies = 37; nindividuals = 1,004) revealed a significant CVA decrease from the follicular to luteal phase (d = −0.39, 95% CI (−0.67, −0.11)). Furthermore, 21 studies allowed for finer-grained comparisons between each of two cycle phases (menstrual, mid-to-late follicular, ovulatory, early-to-mid luteal, and premenstrual). Significant decreases in CVA were observed from the menstrual to premenstrual (nstudies = 5; nindividuals = 200; d = −1.17, 95% CI (−2.18, −0.17)) and from the mid-to-late follicular to premenstrual phases (nstudies = 8; nindividuals = 280; d = −1.32, 95% CI (−2.35, −0.29)). In conclusion, meta-analyses indicate the presence of CVA fluctuations across the menstrual cycle. Future studies involving CVA should control for cycle phase. Recommendations for covarying or selecting cycle phase are provided.
Gesehen am 14.04.2020